Analysis of fiber strain in the human tongue during speech. Issue 8 (10th June 2020) - Gomez, Arnold D.; Stone, Maureen L.; Woo, Jonghye; Xing, Fangxu; Prince, Jerry L.
Abstract: This study investigates mechanical cooperation among tongue muscles. Five volunteers were imaged using tagged magnetic resonance imaging to quantify spatiotemporal kinematics while speaking. Waveforms of strain in the line of action of fibers (SLAF) were estimated by projecting strain tensors onto a model of fiber directionality. SLAF waveforms were temporally aligned to determine consistency across subjects and correlation across muscles. The cohort exhibited consistent patterns of SLAF, and muscular extension-contraction was correlated. Volume-preserving tongue movement in speech generation can be achieved through multiple paths, but the study reveals similarities in motion patterns and muscular action—despite anatomical (and other) dissimilarities.